Geochemical and Magnetic Suseptibility Analysis for Critical Minerals Detection in Igneous Rocks and Beach Sand - Yensi Hariyanto; Siti Zulaikah; Cahyo Aji Hapsoro; Shofi Maulida; Hanif 'Izzudin Zakly; Nordiana Mohd Muztaza; Daeng Achmad Suadi; Aditya Pratama; Hamdi Hamdi (Spektra: Jurnal Fisika dan Aplikasinya, 2024)
Critical minerals are an important natural resource that will continue to be necessary for modern industries. This study aims to determine the distribution of critical minerals based on geochemical data and magnetic susceptibility. Samples were taken from Lenggoksono beach, Southern Malang. The determination of chemical elements was conducted using X-ray fluorescence (XRF). Rare Earth Elements (REE) were identified using Inductively Coupled Plasma–Optical Emission Spectrometry (ICP-OES). Magnetic susceptibility measurements were carried out using a Barrington Magnetic Susceptibility Meter (MS2B). The results showed that the dominant elements were Silica Oxide, SiO2 (70 Wt%), Iron Oxide, Fe2O3 (14.05 Wt%), and Calcium Oxide CaO (5.57 Wt%), which were categorized as critical minerals. The average REE elements detected were Cerium, Ce (6.75 mg/kg), Gadolinium, Gd (5.98 mg/kg), Neodymium, Nd (13.56 mg/kg), Praseodymium, Pr (6.62 mg/kg), Terbium, Tb (5.57 mg/kg), and Yttrium, Y (10.98 mg/kg). The magnetic susceptibility ranges from 13.27 to 4143.47 × 10-8m3/kg. Pearson’s Correlation analysis revealed a significant correlation between low-frequency magnetic susceptibility (ꭓlf) and high-frequency magnetic susceptibility (ꭓhf) with a significance level of 0.01. ꭓlf and ꭓhf also showed a significant correlation with Gd, with a correlation value of R² = 0.84 and a significance level of 0.05. These results indicate that the presence of one critical mineral can serve as a clue to the presence of other critical minerals, and magnetic susceptibility can be used as a proxy indicator for critical minerals in natural materials.